Adaptação do software wiki para informatização da documentação do sistema de gestão da qualidade padrão ISO 9001 - Costal, Graziele Cristina Silveira Zerbini (2012)
Generally, the documentation in compliance with ISO 9001 requirements is a complex task and source of excessive bureaucracy. As a result, the attention that documentation requires can blur the benefits in implementing the standard. In order to overcome that obstacle, the wiki software can be used as an alternative to documentation computerization. Therefore, the objective was to adapt wiki software to computerize the documentation of a ISO 9001 Quality Management System. The method to achieve this goal was to develop a prototype based on wiki (named WikiQMS) with features involving the storage, creation, revision and control of quality documents. Still in the development phase, the prototype was evaluated by an Expert Panel in order to collect their assessments and ideas to improve the prototype. Finally, the WikiQMS was validated and deployed by a junior enterprise Unifei Jr. The result is a wiki prototype that complies with minimum requirements of Quality Management System documentation. The WikiQMS also has many of the Web 2.0 advantages like collaborative editing, collective authorship, accessibility and ease of use, providing a proper environment to documents continuous improvement.